Probing the effect of substrate heating during deposition of DCV4T:C₆₀ blend layers for organic solar cells - Koerner, C; Elschner, C; Selzer, F; Leo, K; Riede, M; Miller, N; Fitzner, R; Reinold, E; Bäuerle, P; Toney, M; McGehee, MD (Elsevier, 2012)
We present a comprehensive investigation of morphological changes inside the active layer of an organic solar cell induced by substrate heating during layer deposition by thermal evaporation in ultra-high vacuum. To explore the trends observed in solar cell devices, we apply absorption and photoluminescence spectroscopy, atomic force microscopy, X-ray diffraction, and organic field effect transistor measurements. The material combination we use comprises unsubstituted dicyanovinyl end-capped quaterthiophene (DCV4T) as the donor material mixed with C60 as the acceptor. The solar cell power conversion efficiency decreases with increasing substrate temperature during film deposition due to changes in the crystalline structure of the oligothiophene phase, leading to a decrease in absorption strength. Photoluminescence measurements show that substrate heating increases the amount of phase separation between the donor and acceptor, and topology and structure investigations reveal large aggregates of polycrystalline DCV4T at the surface. However, the fill factor is increased for higher substrate temperatures due to better transport properties. The highest efficiency obtained with this material combination and stack design is 3.0% under AM1.5g illumination. © 2012 Elsevier B.V. All rights reserved.